Situations-problèmes et disciplines scolaires : analyse des cadres opératoires privilégiés par des futurs enseignants québécois du primaire pour l'enseignement des sciences et des sciences humaines - Johanne Lebrun; Abdelkrim Hasni; Anderson Araújo-Oliveira (Nantes Université, 2011)
Based on research data, this text identifies and analyzes various operational frames favoured by future teachers of primary school in Quebec when it comes to structuring and implementing problem situations in the teaching of sciences and social studies. The analysis shows that the five operational frames identified generate teaching-learning situations that largely mark a departure from the characteristics of a problem situation. These frames share certain common points-namely privileging one or another of the constitutive dimensions of meaning and being underpinned by a pedagogical-didactic and cognitive mediation-which lie on the fringes of disciplinary knowledge and the principle of intelligibility of disciplines. In this sense, despite ministry prescriptions in line with the need for problematized and situated learning, the operational modes of this prescription remain problematic.